Trace elements characterisation in floodplain soils underlain by crystalline rocks, akure, southwestern Nigeria - I.T, Asowata; O.G, Omokolade (International Journal of Advanced Geosciences, 2019)
The results of the floodplain soils study on the spatial distribution of selected trace elements in top soils (0 – 30 cm) and sub soils (> 30 – 100 cm) near Ala River, Akure metropolis, are reported. The objectives of this study are to determine the concentration of trace elements in the top and bottom soils, and identify the possible enrichment sources of these elements in the floodplain area. Forty two samples (top soil 21; sub soil 21) were collected for the study. The samples were air dried at room temperature, disaggregated and sieved using 53 µg mesh size. The prepared samples were further digested using modified aqua regia of (1:1:1 HNO3: HCL: H2O). The digests were subjected to elemental analysis using Inductively Coupled Plasma-Emission Spectrometry (ICP-MS). The trace elements concentration in ppm exhibited the following distribution pattern. Cu range in ppm from 6.0 – 53.0 mean 27.43; Pb, 10.0 – 165.0, mean 58.43; Zn, 29.0 – 479.0 mean 223.1; Ni, 10.0 – 20.0, mean 14.86; Co, 16.0 – 33.0, mean 24.29; Mn, 250.0 – 1615.0, mean 983.29; Th 9.0 – 19.0, mean 14.43; V, 35.0 – 89.0, mean 73.05; La 26.0 – 84.0, mean 56.76 and Cr 11.0 – 60.0 mean 40.43. While the result for the sub soils range in ppm, Cu from 3.0 – 51.0, mean 21.24; Pb, 7.0 – 208.0, mean 56.33; Zn, 21.0 - 460.0. mean 149.14; Ni, 8.0 – 29.0, mean 13.76; Co, 12.0 – 37.0, mean 23.95; Mn, 138.0 – 2283.0, mean 806.43; Th 9.0 – 28.0, mean 17.48; V, 40.0 – 105.0, mean 68.71; La 25.0 – 96.0, mean 61.00 and Cr 12.0 – 58.0 mean 35.38. The results of both the top soils and sub soils showed higher concentration metal enrichment than the average shale values. The relative elemental mean concentration is such that Mn> Zn > V > La > Pb > Cr > Co > Cu > Th > Ni in that order. Elements such as Cu, Zn, Pb, V, Mn, Th and Cr had relatively moderate to very strong correlation coefficient (r = 0.54 0.97) with each other, which apparently indicate that these elements are of same source of enrichment in the floodplain. Pb, Zn, V, La, Th and Cr are elements that are of significant environmental concerns.